CFTR modulates RPS27 gene expression using chloride anion as signaling effector - Valdivieso, Ángel Gabriel (2017)
In Cystic Fibrosis (CF), the impairment of the CFTR channel activity leads to a variety of alterations, including differential gene expression. However, the CFTR signaling mechanisms remain unclear. Recently, culturing IB3-1 CF cells under different intracellular Cl− concentrations ([Cl−]i), we observed several Cl−-dependent genes and further characterized one of them as RPS27. Thus, we hypothesized that Cl− might act as a signaling effector for CFTR signaling. Here, to test this idea, we study RPS27 expression in T84 cells modulating the CFTR activity by using CFTR inhibitors. First, we observed that incubation of T84 cells with increasing concentrations of the CFTR inhibitors CFTR(inh)-172 or GlyH-101 determined a progressive increase in the relative [Cl−]i (using the Cl− fluorescent probe SPQ). The [Cl−]i rise was concomitant with a dose-dependent down-regulation of RPS27. These results imply that CFTR inhibition produce Cl− accumulation and that RPS27 expression can be modulated by CFTR inhibition. Therefore, Cl− behaves as a signaling effector for CFTR in the modulation of RPS27 expression. In addition, the IL-1β receptor antagonist IL1RN or the JNK inhibitor SP600125, both restored the down-regulation of RPS27 induced by CFTRinh-172, implying a role of autocrine IL-1β and JNK signaling downstream of Cl− in RPS27 modulation.